2014
DOI: 10.1194/jlr.m043646
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl ester transfer proteins from different species do not have equivalent activities

Abstract: This article is available online at http://www.jlr.org homologs in more than 20 species. In species where CETP activity has been experimentally verifi ed, this is typically based solely on the presence of CE transfer activity in plasma. Mutagenesis studies have shown that minor changes in the structure of human CETP can have profound effects on its ability to bind lipoproteins or selectively alter its ability to utilize TG and/or CE as a transfer substrate ( 5, 6 ). Given this, it seems likely that CETP from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…By this mechanism CETP facilitates either the exchange of like lipid molecules (homoexchange) or the exchange of different lipids (heteroexchange). However, we previously reported that under nonphysiologic conditions where the acceptor particle lacks neutral lipid substrate, that CETP-mediated lipid transfer is greatly reduced, but there remains a low level of lipid transfer to these neutral lipid-null particles ( 5,10 ). These results show that CETP is capable of delivering CE or TG to an acceptor particle and leaving the particle surface without picking-up any TG or CE, thus mediating a one way transfer.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…By this mechanism CETP facilitates either the exchange of like lipid molecules (homoexchange) or the exchange of different lipids (heteroexchange). However, we previously reported that under nonphysiologic conditions where the acceptor particle lacks neutral lipid substrate, that CETP-mediated lipid transfer is greatly reduced, but there remains a low level of lipid transfer to these neutral lipid-null particles ( 5,10 ). These results show that CETP is capable of delivering CE or TG to an acceptor particle and leaving the particle surface without picking-up any TG or CE, thus mediating a one way transfer.…”
Section: Discussionmentioning
confidence: 63%
“…The x-axis units are TG/(TG + CE). When expressed this way, the substrate preference ratio for human CETP is 0.33 instead of the ‫ف‬ 0.5 value shown in Table 2 and also previously reported ( 10 ). Results are the mean ± SD of multiple experiments as follows: R201S (two), M433A (one), H232A (fi ve), wild-type human (seven), monkey (two), rabbit (two), Q199A (six), hamster (two).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations